Shifts in soil C stabilization mechanisms are linked to reindeer-induced changes in plant communities and associated fungi in subarctic tundra - Tyvijärvi, Anne; Stark, Sari; Ylänne, Henni; Castaño, Carles; Adamczyk, Bartosz (Elsevier, 2024)
Arctic tundra ecosystems store a significant proportion of the global soil organic carbon (C). However, warming-induced shrub encroachment and reindeer (Rangifer tarandus L.) grazing regimes promoting graminoid vegetation may strongly influence tundra soil C stability. Here, we studied how reindeer grazing intensity and experimental warming affect soil C stabilization in a tundra ecosystem. We hypothesized that under light grazing, persistent complexes formed by fungal necromass (FNM) and condensed tannins (CT) from shrub roots stabilize the soil C, whereas, under heavy grazing, the soil C stabilization is affected by glomalin-related soil proteins (GRSP) produced by arbuscular mycorrhizal fungi of graminoids. In addition, we expect warming to mediate grazing effects, diminishing the potential for C stabilization. Our results show no effect of grazing on stable C concentration, however, under light grazing the labile C concentration was higher. We found higher concentrations of chitin and tannins under light grazing, indicative of soil C stabilization potential through FNM-CT complexes. By contrast, we found more root ergosterol under heavy grazing, suggesting a high abundance of endophytes, usually melanized, and a slightly higher GRSP concentration. Warming did not cause changes in stable C concentration but was associated with changes in the soil chemical quality, pointing to a decrease of lignin, polypeptides, and polysaccharides. We conclude that different soil C stabilization mechanisms operate under light and heavy grazing pressures and that these mechanisms are closely linked to changes in the vegetation and the fungi typically associated with them.
Keywords: soil carbon stabilization; grazing intensity; plant communities; fungi